Struggling with modernity - British Broadcasting Corporation; Ambrose Video Publishing (New York : Ambrose Video Publishing, 1993)
'Looks at the tensions within Islamic states as they attempt to make their laws and practices compatible with the 21st century while remaining true to the spirit of the faith'--container
Film editor, Peter Miller ; videotape editor, Peter Dunkley ; music, Rohan ; consultant, Akbar Ahmed
Host: Akbar Ahmed
Keywords: Islamic ethics; Women in Islam; Muslims -- Intellectual life